2019
DOI: 10.1007/s00464-019-06961-1
|View full text |Cite
|
Sign up to set email alerts
|

3D laparoscopy does not reduce operative duration or errors in day-case laparoscopic cholecystectomy: a randomised controlled trial

Abstract: Background Contemporary 3D platforms have overcome past deficiencies. Available trainee and laboratory studies suggest stereoscopic imaging improves performance but there is little clinical data or studies assessing specialists. We aimed to determine whether stereoscopic (3D) laparoscopic systems reduce operative time and number of intraoperative errors during specialist-performed laparoscopic cholecystectomy (LC). Methods A parallel arm (1:1) randomised controlled trial comparing 2D and 3D passive-polarised l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 35 publications
0
4
0
Order By: Relevance
“…3D laparoascopy was reported to shorten operative time and enhance depth perception in five randomised studies analysed for a systematic review [26]. However, a recent randomised trial by Schwab et al [27] concluded that 3D laparoscopy did not reduce overall operative time or error frequency in LC performed by specialist surgeons. In agreement with our findings, they observed that case difficulty, according to the Nassar Scale, was a major confounding variable with a larger impact on operative time than the imaging system used.…”
Section: Discussionmentioning
confidence: 99%
“…3D laparoascopy was reported to shorten operative time and enhance depth perception in five randomised studies analysed for a systematic review [26]. However, a recent randomised trial by Schwab et al [27] concluded that 3D laparoscopy did not reduce overall operative time or error frequency in LC performed by specialist surgeons. In agreement with our findings, they observed that case difficulty, according to the Nassar Scale, was a major confounding variable with a larger impact on operative time than the imaging system used.…”
Section: Discussionmentioning
confidence: 99%
“…As lap chole's learning curve smoothed out, the incidence of VBI stayed under control and no such leak was seen throughout the entire trial period [ 8 , 9 ]. However, according to recent data, mortality and morbidity have not altered considerably, but BDI has been increasing for a number of years (0.32 to 0.52) [ 10 , 11 ].…”
Section: Discussionmentioning
confidence: 99%
“…Some researchers have pointed out the obvious superiority of 3D laparoscopy over 2D laparoscopy for complex surgery (e.g., oncological, urological, and bariatric surgery) [ 19 - 21 ]. However, some randomized studies revealed no differences in the performance of cholecystectomy, hernioplasty, or appendectomy between these two laparoscopic methods [ 22 , 23 ]. We consider laparoscopic donor nephrectomy to be one of the most complex operations; moreover, in this procedure, healthy donors with altruistic motivations are subjected to surgical interventions and risks without any expected therapeutic effects.…”
Section: Discussionmentioning
confidence: 99%